Government Coordination In Anticipation of The Mount Merapi Eruption Disaster In Sleman Regency, DIY - Heru Sulistiyo; Arwanto Harimas Ginting; Agus Winarna; Kusworo (Dinasti Research, 2026)
The eruption of Mount Merapi poses a significant disaster threat to Sleman Regency, necessitating a paradigm shift from emergency response to disaster risk reduction through synergistic government coordination. This article aims to analyze the forms and mechanisms of government coordination in anticipating the Mount Merapi eruption, identify obstacles, and formulate strategies for improvement. Employing a qualitative descriptive method, this study examines coordination based on Herbert Simon's procedural and substantive typology, alongside collaborative governance concepts. The findings indicate that procedural coordination is established through structured regulations, hierarchical command, and the Cross-Merapi Joint Secretariat collaboration. Substantively, preparedness is realized through the Sister Village program and the pentahelix-based utilization of the SIMANTAB application. However, coordination effectiveness is hindered by sectoral egos, rigid budgetary bureaucracy, personnel limitations, and cultural resistance among locals. Therefore, the study recommends cross-sectoral data synchronization, the debureaucratization of emergency decision-making, and an inclusive cultural mitigation approach to achieve adaptive regional resilience.